Grammatical Accuracy using Teacher’s Written Corrective Feedback - Solfiyatuzzahro Solfiyatuzzahro; Asih Santihastuti; Erfan Erfan (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2019)
The purpose of this research was to improve grammatical accuracy on writing descriptive text by using Teacher’s Written Corrective Feedback and to know their perceptions toward the application of the technique in teaching writing. This research design was a classroom action research that was conducted collaboratively with the English teacher. The result of the data analysis revealed that the application of Teacher’s Written Corrective Feedback could improve the tenth grade students’ grammatical accuracy. The improvement of students’ grammatical accuracy could be seen from the percentage of students who got score ≥ 71 increased from 72% in the first cycle to 78% in the second cycle. The students’ accuracy could be seen from the improvement of grammar accuracy in each grammatical aspect. The result showed that students’ grammar score highly improved in present tense and noun/pronoun aspects. Teacher’s Written Corrective Feedback and the procedure used such as additional explanation from teacher and revision process could help the students improve their grammatical accuracy in writing. Besides, students thought Teacher’s Written Corrective Feedback had favorable impact which it was beneficial and meaningful for them to overcome their difficulties in writing and to make them aware of their errors.